Culture and the politics of Third World nationalism - Dawa Norbu, 1949- (Routledge, 1992)
Nationalism in specific political systems combined with a theoretical framework that draws out its universal significance. Ten case studies from South Asia, the Middle East, Latin America and Europe focus on local cultural factors.